Determinación del Índice de Higiene Oral Simplificado en niños menores de 5 años de la parroquia Manú, cantón Saraguro, provincia de Loja - Paredes Córdova, Ligia Elena (2022)
Oral hygiene is the set of knowledge and practical cleaning skills in the oral cavity, which allow preventing the appearance of oral pathologies, and maintaining the oral and general health of the individual. Children under 5 years of age in the town of Manú, in Saraguro County in the Loja province are a high-risk group and have a high rate of oral pathologies, such as dental cavities and gingivitis, due to inappropriate oral hygiene; what contributes to this is a lack of oral education and resources for cleaning teeth properly. The purpose of this study was: determine the simplified oral hygiene index in children under 5 years of age; indicate the sex of the child and the tooth with the greatest accumulation of biofilm and dental calculus. Through a quantitative, descriptive and cross-sectional study carried out on 79 children under 5 years of age, the dental clinical history of Pediatric Dentistry of the National University of Loja was used, in which, through the interpretation of the acquired data, the Oral Hygiene Index Simplifled (OHIS) was evaluated; the collected data was processed with the version 28.0 statistical program SPSS (Statistical Package for the Social Sciences). The results obtained were: that 53.17% of the sample exhibited a regular OHIS; there was no significant difference between males and females in the indices of bacterial plaque (IBP) and dental calculus (DC) and; the dental piece with the most presence of bacterial plaque was number 65 and the one with the greatest accumulation of dental calculus was number 85. Thus, concluding that most of the children of the Manú town had regular oral hygiene regardless of gender